1994
DOI: 10.1126/science.7973634
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea as an Inhibitor of Human Immunodeficiency Virus-Type 1 Replication

Abstract: Hydroxyurea, a drug widely used in therapy of several human diseases, inhibits deoxynucleotide synthesis--and, consequently, DNA synthesis--by blocking the cellular enzyme ribonucleotide reductase. Hydroxyurea inhibits human immunodeficiency virus-type 1 (HIV-1) DNA synthesis in activated peripheral blood lymphocytes by decreasing the amount of intracellular deoxynucleotides, thus suggesting that this drug has an antiviral effect. Hydroxyurea has now been shown to block HIV-1 replication in acutely infected pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
170
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(177 citation statements)
references
References 26 publications
6
170
0
1
Order By: Relevance
“…To this end, ␤-chemokine production by activated PBMCs cultured in the presence of HU was investigated. HU is a cytostatic drug that, by depleting intracellular nucleotide pools, arrests cell cycle progression in late G 1 (9). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, ␤-chemokine production by activated PBMCs cultured in the presence of HU was investigated. HU is a cytostatic drug that, by depleting intracellular nucleotide pools, arrests cell cycle progression in late G 1 (9). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggested that the antiviral effect observed was not due to inhibition of the virus reverse transcription step by HU-mediated depletion of nucleotide pools. Although it is known that HU exerts anti-HIV-1 activity by reducing the intracellular nucleotide pools (15), low concentrations of the drug (Յ100 M) are effective only when combined with nucleoside analog reverse transcription inhibitors (9). Therefore, our results showing little antiviral activity by 100 M HU when added to fresh culture medium agree with previous reports and indicate further that the increase in chemokine levels resulting from exposure to the drug is the likely explanation for the antiviral effect observed.…”
Section: Discussionmentioning
confidence: 99%
“…Thapsigargin, which blocks the cell cycle at G 0 , did not consistently reduce lymphoproliferation or p24 antigen production. Hydroxyurea inhibits HIV-1 replication (Lori et al, 1994) and has been used in combination with dideoxynucleoside reverse transcriptase inhibitors for the treatment of HIV-1 infection (Lori & Lisziewicz, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the two-LTR circular form was not detected until 8 h after infection, when the majority of cells have passed through mitosis. Because HUand not aphidicolin-inhibits deoxynucleotide synthesis and consequently blocks HIV-1 DNA synthesis by decreasing the amount of intracellular deoxynucleotides (31), it is a reasonable explanation for the lack of two-LTR detection in this In support of this hypothesis is the fact that in vitro direct ligation of the ends of HIV-1 linear DNA molecule with cytoplasmic extracts is induced by incubation of the extracts in the presence of added deoxynucleoside triphosphates. To the contrary, no two-LTR junctions were detected when extracts were incubated in the absence of added deoxynucleoside triphosphates (15).…”
Section: Discussionmentioning
confidence: 94%